Nonlinear Damping as the Fourth Dimension in Optical Fiber Anemometry - Jeremiah C. Williams; Hengky Chandrahalim (Advanced Sensor Research)
Abstract In this study, nonlinear damping is introduced as the fourth dimension in the operation of a fiber tip optomechanical anemometer. The flow sensing element, featuring a 3D rotor measuring 110 µm in diameter and fabricated through a two‐photon nanomachining process, is monolithically integrated onto the cleaved face of the optical fiber, which serves as an integrated waveguide. As the rotor encounters airflow, it spins, and mirrors on its blades reflect light across the fiber core at each pass. This setup permits precise measurement of gaseous fluid flow with minimal sensor footprint at the point of detection and accommodates a variety of optical sources and measurement apparatuses without the need for specific wavelength or broad‐spectrum capabilities. To stabilize the rotation of the rotor and facilitate consistent frequency‐domain analysis, a polydimethylsiloxane hydrocarbon stabilizing agent is infused into the gap between the rotor and stator of the sensing element via dual‐function microfluidic channels. This enhancement allows for the measurement of gaseous nitrogen flow rates from 10 to 20 liters per minute (LPM), with a consistent periodic response. Comprehensive characterizations of the fiber tip anemometer are presented with and without the stabilizing medium, demonstrating its crucial role in regulating the dynamics between the rotor and the stator.